PARTISIPASI MASYARAKAT DALAM PEMBAYARAN PAJAK KENDARAAN BERMOTOR (PKB) MELALUI E-SAMSAT SELAMA PANDEMI COVID-19 DI BAPENDA SULAWESI SELATAN - Sri Wisdayanti; Muthiah Hurmaniah Burhanuddin; Iswaningsi Rezki Amaliah; Hendrawati Hamid (Jurnal Pallangga Praja (JPP), 2022)
This study aims to analyze public participation in the payment of Motor Vehicle Tax (PKB) in Makassar Cityfor the last three years and the inhibiting factors. This study uses a qualitative descriptive method with datacollection techniques in the form of observation and interviews. This research was conducted from May 11to June 2, 2022. The object of the research is the Regional Revenue Agency of South Sulawesi Province,SAMSAT UPT Makassar, and motorized vehicle taxpayers. The results showed that e-SAMSAT had an effecton the level of acceptance of PKB and ease of administration for the people of Makassar City. the BOD.E-SAMSAT for the community’s economy through the Motor Vehicle Tax sector during the pandemic withtax realization in 2020-2021 increasing by 3.51% for Makassar City